The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11858-015-0707-2
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding mathematical modelling with a solution plan

Abstract: world (Blum et al. 2007). Modelling is of high importance for students' current and future life and is, for example, an important part of the NCTM principles and standards for school mathematics (National Council of Teachers of Mathematics 2000). Students from different countries all over the world are required to learn how to solve modelling problems. However, a number of empirical studies show that many students have an insufficient level of modelling competency by the end of lower secondary education (Blum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 36 publications
1
38
0
12
Order By: Relevance
“…The results show the potential of the solution plan as guideline: The students using the solution plan while working on the modelling problem reported that they used strategies more frequently than those of the control group. Furthermore, students using the solution plan showed higher achievement than those in the other group (Schukajlow et al , 2015a.…”
Section: Classroom Settingsmentioning
confidence: 85%
“…The results show the potential of the solution plan as guideline: The students using the solution plan while working on the modelling problem reported that they used strategies more frequently than those of the control group. Furthermore, students using the solution plan showed higher achievement than those in the other group (Schukajlow et al , 2015a.…”
Section: Classroom Settingsmentioning
confidence: 85%
“…Several studies report promising qualitative or observational results that provide proof of principle. Only a few have experimental results that show the effectiveness of their approach (e.g., Fisher et al, 2013;Kajamies et al, 2010;Roll et al, 2012;Schukajlow et al, 2012Schukajlow et al, , 2015. In our view it is therefore too early for a systematic quantitative review study such as meta-analysis of the scaffolding research (cf.…”
Section: Effectivenessmentioning
confidence: 99%
“…Hard scaffolds are static ones given beforehand. Among the successful hard scaffolds are solution plans (Schukajlow et al, 2015), proof flow charts (Miyazaki et al, this issue) and worked-out examples (Tropper et al, 2015). Soft scaffolds are dynamic and used on-the-fly.…”
Section: What Is Scaffolded?mentioning
confidence: 99%
“…This appears to be particularly so regarding the phases of orientation and organisation, in that students often find it difficult to thoroughly understand the problem situation (cf. Goos, Galbraith & Renshaw, 2002;Stylianou & Silver, 2004) and to plan how to solve a problem (Pugalee, 2001;Schukajlow, Kolter & Blum, 2015). Research on this subject now focuses in particular on developing useful tools (e.g.…”
Section: Orientation and Organisation Phases In The Problem-solving Pmentioning
confidence: 99%